A prospective study of magnetic resonance imaging findings in patients of chronic low back pain: a clinico-radiological correlation - Rai, Garjesh Singh; Mehra, Alankrita; Gaur, Tribhuwan Narayan Singh (International Journal of Research in Medical Sciences, 2016)
Background: Low back pain (LBP) is one of most commonly presenting complaint related to musculoskeletal system and affecting mostly middle aged and older person but now a day’s younger people are also suffering. Correlation of clinical signs and symptoms with magnetic resonance imaging (MRI) findings is very helpful to find out exact cause of pain and its management. The aim and objective of the study was to correlate the MRI findings with clinical findings of patient and to assess the pattern and spectrum of MRI findings in various degenerative diseases in lumbar spine. Methods: This institution based prospective observational study had been performed among 100 selected patients in 2yrs period in between April 2013 to April 2015 who presented with chief complaint of chronic LBP. Clinical history of all patients had been taken in detail. Clinical test i.e. SLR and Lasegue’s tests have been performed in all patients. MRI of lumbosacral spine (L-S spine) had been performed in 1.5 Tesla Siemens magnetom vision plus MRI scanner. Results: Total 100 patients of 20 to 80-year age group had been selected with mean age of 50.5yr. Among 100 patients; 68 males and 32 females had participated in the study. The most common degenerative finding was desiccation of disc followed by disc bulge, disc herniation, spinal canal stenosis, ligamentum flavum hypertrophy, facet joint hypertrophy, osteophytes and modic changes. L4-L5 and L5-S1 was the most commonly involved spinal levels in any degenerative pathology. Conclusions: Significant association has been observed between MRI L-S spine finding and clinical findings in most of the patients of chronic low backache however in few patient clinico-radiological correlations could not be matched completely.